Nurse educators and student nurses' perspectives on ways to improve implementation of simulation-based education in Lesotho - Pule S. Moabi; Ntombifikile G. Mtshali (AOSIS, 2022)
Background: In order to ensure an effective health system, there is a need to recruit, train and deploy a competent nursing workforce. A competent workforce can be made possible by integrating simulation into the curriculum. Implementation of simulation-based education in Lesotho is facing a number of challenges as the country has limited resources. Objectives: This study aimed to describe nurse educators and students' perspectives on ways to improve implementation of simulation-based education in Lesotho. Method: A qualitative study was conducted. A total of 24 students, 24 nurse educators and 4 principals who were purposely selected participated in the study. Focus group discussions as one of the data collection methods were used to collect data from the nurse educators and students whilst in-depth, unstructured individual interviews were used with the principals. Data were analysed following the Corbin and Strauss grounded theory approach where similar codes were categorised together as part of open coding, and axial coding was conducted by refining the codes and organising them into categories and subcategories. Results: Two categories emerged from the areas where improvement is required: resources to support simulation. Resources emerged as playing a major role in ensuring quality simulation. The teaching and learning process emerged as collaborative in nature with all key players ensuring that they meet their responsibilities in order to ensure effective simulation-based learning. Conclusion: The study revealed that there are limited numbers of simulation facilitators and this hinders effective implementation of simulation. Students are concerned about the comments of educators during simulation, as some of the comments are belittling.